2018
DOI: 10.1002/dc.23905
|View full text |Cite
|
Sign up to set email alerts
|

Immediate biopsy of cervical cytology‐negative and non‐HPV‐16/18 oncogenic types positive patients

Abstract: For the patients who had cervical cytology negative/non-HPV-16/18 positive, we detected that 1.1% of these women had CIN 2-3. For this reason, by chasing the algorithm recommended by guidelines, gynecologists take risk missing a diagnosis of CIN 2 plus lesion in 1.1% of patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 19 publications
0
14
3
Order By: Relevance
“…Aydoğmuş and Aydoğmuş (9) reported that the ratio of CIN 2+ lesions in cases of normal cytology results with non-16/18 HPV subtypes was 15.6%. Conversely, in another research, this ratio was reported as 0.01% (10). Our research detected CIN 2+ lesions 4% of patients with negative cytology.…”
Section: Discussioncontrasting
confidence: 71%
“…Aydoğmuş and Aydoğmuş (9) reported that the ratio of CIN 2+ lesions in cases of normal cytology results with non-16/18 HPV subtypes was 15.6%. Conversely, in another research, this ratio was reported as 0.01% (10). Our research detected CIN 2+ lesions 4% of patients with negative cytology.…”
Section: Discussioncontrasting
confidence: 71%
“…In the present study, the rates of presence of CIN 2+ and CIN 3+ lesions are more than the immediate risk of CIN 2+ and CIN 3+ for patients with HPV‐positive and NILM cytology reported in the 2019 ASSCP guideline. In another study of 169 patients with non‐HPV‐16/18 oncogenic types and negative cytology, 151 patients (89%) had no dysplasia, 16 patients (9.4%) had CIN 1, and 2 patients (1.1%) had CIN 2/3 24 . Vargas et al re‐evaluated 121 non‐16/18 hrHPV positive/cytology negative patients with co‐test at least one year later.…”
Section: Discussionmentioning
confidence: 99%
“…We also determined that HPV 16/18 and oncogenic types significantly differed in terms of endocervical curettage biopsy results. Clinicians should consider that the possibility of cervical intraepithelial neoplasia is 23.8% for LGSIL and 6.2% for HGSIL in colposcopic biopsy and 4.3 % for LGSIL and 1.1% for HGSIL in endocervical curettage [31,32]. To reduce mortality and morbidity related to cervical cancer, more precise algorithms should be constituted [33].…”
Section: Discussionmentioning
confidence: 99%